Analisis Faktor-Faktor Yang Berpengaruh Pada Keterlambatan Penyampaian Hasil Audit - Ardianingsih, Arum; Langelo, Juandy Seiver (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Audited financial reports must be published by companies registered and traded on the stock exchange market on the Indonesia Stock Exchange. The length of time the audit of financial statements is carried out by the auditor sometimes makes the audited financial statements late for publication or commonly called audit delay. This study aims to provide empirical evidence regarding the effect of profitability, auditor gender, IFRS convergence and reputation KAP on audit delay. The research was conducted on banking sub-sector listed on the Indonesia Stock Exchange 2016-2017 period. The research method used a quantitative approach. The source of this research used secondary data sourced from the annual report of various sector companies in the banking sub-sector listed on the Indonesia Stock Exchange. The research data was taken using purposive sampling. The analysis technique is done by classical assumption test, multiple linear regression. The results of the study found that Auditor gender hasn`t significant negative effect on audit delay. IFRS convergence hasn`t significant negative effect on audit delay. Reputation KAP has a significant negative effect on audit delay. The implication of the research results is that companies going public and listed on the IDX can appoint a KAP with a good reputation and it is recommended that the implementation of IFRS convergence is carried out earlier.